Roundtable Report: Migration and Security: September 11 and Implications for Canada’s Policies - Bhattacharyya, Suman (Refuge: Canada’s Journal on Refugees, 2002)
On March 15, 2002, the Canadian Centre for Foreign Policy Development, in partnership with the Centre for Refugee Studies at York University, held a roundtable meeting in Toronto to assess the implications for Canada’s policies concerning migration resulting from the terrorist attacks of September 11. The purpose of this event was to draw on the knowledge and insight of participants from a wide range of civil society sectors to inform policy development. Discussants proposed a coherent framework for Canada’s migration policy that emphasizes the safety and well-being of migrants. Policy advice generated from this roundtable concerns Canada’s overall approach to migration policy; Canada’s immigration and refugee system; and continental and international implications for Canada’s policies.